Chemical Composition and Medicinal Significance of Ageratum conyzoides: A Review - Singhal, Peeush (International Journal of Pharmaceutical & Biological Archive, 2021)
The plant Ageratum conyzoides L. family Asteraceae is locally known as billygoat weed and Sadhandhi in India. It is used as traditional medicine for the treatment of numerous ailments such as analgesic, antifungal, wound healing, anti-inflammatory, hemostatic, smooth muscle relaxant, and anticoagulant activity. The plant has several phytoconstituents such as trans-cadina-1(6), 4-diene, hexanal, Î²-copaene, caryophylla-4(12), 8(13)-diene-5-Î²-ol and 1, 10-di-epi-cubenol. Evan through many of the investigational studies validated its traditional therapeutics uses, but unemployed uncharacterized crud extracts. Pharmacological activities of plant extracts and individual phytoconstituents have discovered analgesic, antifungal, wound healing, anti-inflammatory, hemostatic, smooth muscle relaxant, and anticoagulant activity. The results of few pharmacological studies and bioactive metabolites already reported in A. conyzoides. Hence, in the view of huge remedial worth of the plant, current review is therefore bringing together all the information related to the A. conyzoides.